Hariraya [videorecording] : Mindanao tapestry. (Quezon City : Felta.)
Learn the popular native dance. regional dances from the highlands up to Mindanao. Interpreted by a popular dance group in its native costumes.
Keywords: Folk dancing, Philippines -- Mindanao